2022
DOI: 10.5217/ir.2020.00146
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker dynamics during infliximab salvage for acute severe ulcerative colitis: C-reactive protein (CRP)-lymphocyte ratio and CRP-albumin ratio are useful in predicting colectomy

Abstract: cerative colitis (ASUC) is a severe exacerbation of UC that warrants intravenous corticosteroids and may require emergency colectomy. 3 Corticosteroid failure necessitates salvage therapy with infliximab or ciclosporin which have demonstrated good short term efficacy. [4][5][6][7] However longer term prognosis after medical salvage remains guarded, where up to 50% of patients still proceed to colectomy in the absence of maintenance biologic therapy. [8][9][10] Conversely, a proportion of patients may have an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…CRP level has been suggested as a predictor of poor outcome in UC patients 27 and considered a biomarker of response to IFX induction therapy. 28,29 Endoscopic finding is also one of the major factors determining the severity and prognosis of UC. In this study, the baseline CRP levels were lower in responders than in nonresponders, though without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…CRP level has been suggested as a predictor of poor outcome in UC patients 27 and considered a biomarker of response to IFX induction therapy. 28,29 Endoscopic finding is also one of the major factors determining the severity and prognosis of UC. In this study, the baseline CRP levels were lower in responders than in nonresponders, though without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies employed NLR as a potential tool to predict post-surgical hospital stay or development of various complications in CD [84,[98][99][100][101], UC [93,[102][103][104][105], or IBD [106,107].…”
Section: Nlr To Predict Length Of Post-operative Hospital Stay and Ibd Complicationsmentioning
confidence: 99%
“…In a subset of patients with UC who underwent IPAA, Fleshner et al [105] determined that higher NLR was associated with increased rates of de novo CD as a defined post-surgical complication (p = 0.03). In patients treated with IFX salvage for steroid-refractory acute severe UC, Con et al [103] reported a weak but significant correlation between day 3 NLR and colectomy within twelve months (p = 0.020); NLR value upon admission and on day 1 were not associated with subsequent colectomy (p = 0.340 and 0.792, respectively). Similarly, Andrew et al [93] did not find a correlation between NLR and colectomy after hospital admission prior to or one day following IFX salvage therapy (r = −0.01 and −0.01, respectively; correlation method not specified).…”
Section: Nlr To Predict Length Of Post-operative Hospital Stay and Ibd Complicationsmentioning
confidence: 99%
“…In an Irish study of 124 patients with acute severe UC, CAR was significantly higher in steroid-refractory patients than in steroid-responsive patients [ 15 ]. In an Australian retrospective study of steroid-refractory UC patients, CAR was positively associated with colectomy after infliximab [ 16 ]. Taking these results together, CAR is positively associated with clinical activity, endoscopic activity, and poor response to medication in UC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have reported an association between the C-reactive protein (CRP)-to-albumin ratio (CAR), a useful serum marker for several other diseases [ 8 12 ], and UC [ 13 16 ]. Evidence regarding the association between CAR and clinical outcomes in UC remains scarce, however.…”
Section: Introductionmentioning
confidence: 99%